2021
DOI: 10.1021/acsami.1c19158
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Protection Layers via a Self-Driven Chemical Reaction To Stabilize Lithium Metal Anodes

Abstract: The Li metal anode is considered one of the most potential anodes due to its highest theoretical specific capacity and the lowest redox potential. However, the scalable preparation of safe Li anodes remains a challenge. In the present study, a LiF-rich protection layer has been developed using self-driven chemical reactions between the Li3x La2/3–x TiO3/polyvinylidene fluoride/dimethylacetamide (LLTO/PVDF/DMAc) solution and the Li metal. After coating the LLTO/PVDF/DMAc solution to Li foil, PVDF reacted with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…High interfacial resistance with lithium leads to lower power output and low efficiency. Perovskite has the general formula ABO 3 (A = Ca, Sr or La; B = Al, Ti) [58]. The most studied perovskite electrolyte is Li 3x La 2/3−x TiO 3 (LLTO), with bulk Li+ ion conductivity of 10 −3 S. cm −1 at 25 • C [59].…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…High interfacial resistance with lithium leads to lower power output and low efficiency. Perovskite has the general formula ABO 3 (A = Ca, Sr or La; B = Al, Ti) [58]. The most studied perovskite electrolyte is Li 3x La 2/3−x TiO 3 (LLTO), with bulk Li+ ion conductivity of 10 −3 S. cm −1 at 25 • C [59].…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…The organic-inorganic hybrid film in combining the merits of each component is an alternative solution to effectively protect Li metal anode. [149][150][151] Dense and highly conductive inorganic components are much involved, such as LiF, [148,152,153] Li 2 O, [154] Li 2 S, [155][156][157] etc. An efficient multifunctional silanization interface on the Li metal anode surface was constructed for high-energy Li metal pouch cells.…”
Section: Designing Artificial Seimentioning
confidence: 99%
“…Organic-inorganic hybrid film was proposed to integrate the merits of organic and inorganic components. [149][150][151] 2D materials were often adopted in the composite film due to their high strength and ionic conductivity, as well as a facile assembly process, such as vermiculite, [164,165] graphene oxide, etc. Specifically, 2D materials can accelerate Li-ion hopping at the surface between polymer chains and functionalized inorganic contents as well as reduce the crystallization degree of organic contents by these inorganic contents, thereby enhancing the Li-ion conductivity.…”
Section: Designing Artificial Seimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ionic conductivity of PEO‐based SPEs (in the range of 10 −7 to 10 −6 S cm −1 ) is far lower than that of liquid electrolytes (~10 −2 S cm −1 ) owing to its high crystallinity at room temperature (RT) and the intrinsically low mobility of polymer chains 13,14 . Several strategies have been attempted to overcome this deficiency, including the fabrication of cross‐linked/interpenetrating‐network PEO‐based copolymers, 11,15–18 and the addition of functional fillers to PEO matrix 19–22 . In‐depth investigations have revealed that active nanofillers could provide additional Li + transfer pathways in SPEs and elevate the Li + concentration in the space‐charge region at the filler/polymer interface 23 .…”
Section: Introductionmentioning
confidence: 99%